2022
DOI: 10.1038/s41380-022-01700-w
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in TRN-anterodorsal thalamocortical circuits affect sleep architecture and homeostatic processes in oxidative stress vulnerable Gclm−/− mice

Abstract: Schizophrenia is associated with alterations of sensory integration, cognitive processing and both sleep architecture and sleep oscillations in mouse models and human subjects, possibly through changes in thalamocortical dynamics. Oxidative stress (OxS) damage, including inflammation and the impairment of fast-spiking gamma-aminobutyric acid neurons have been hypothesized as a potential mechanism responsible for the onset and development of schizophrenia. Yet, the link between OxS and perturbation of thalamoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 139 publications
0
10
0
Order By: Relevance
“…[68][69][70][71][72][73] In addition, several preclinical models relevant to the study of neuropsychiatric illnesses have also noted reduced sleep spindle density in rodents. 43,74,75 Of note is that sleep spindle spectra power during KYNA elevation was initially reduced in the lower sigma range and, perhaps as a consequence of an increased cortical drive to ameliorate reduced spindle density, the power spectra was then elevated in the upper sigma range in male subjects. 76 Yet importantly, prophylactic treatment with PF-04859989 effectively ameliorated kynurenine-induced sleep deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72][73] In addition, several preclinical models relevant to the study of neuropsychiatric illnesses have also noted reduced sleep spindle density in rodents. 43,74,75 Of note is that sleep spindle spectra power during KYNA elevation was initially reduced in the lower sigma range and, perhaps as a consequence of an increased cortical drive to ameliorate reduced spindle density, the power spectra was then elevated in the upper sigma range in male subjects. 76 Yet importantly, prophylactic treatment with PF-04859989 effectively ameliorated kynurenine-induced sleep deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the TRN, non-sensory thalamocortical networks including the intralaminar and central medial thalamus, anterior dorsal, and frontal cortices have received relatively less investigation. However, both animal models and human studies have demonstrated that sleep spindles are involved in the regulation of cognitive functions such as attention, executive control, and higher-order sensory processing [ 10 , 14 , 15 , 66 – 69 ]. While there are signs of common regulatory processes with sensory networks, molecular, genetic investigations have found distinct components and signaling pathways that drive the formation of non-sensory thalamocortical circuits [ 11 , 17 , 60 62 , 71 , 72 ].…”
Section: Development Of Sleep Spindlesmentioning
confidence: 99%
“…Glutamate‐cysteine ligase is the key glutathione synthesis 1 . Treatment with N ‐acetylcysteine, a precursor of endogenous antioxidant glutathione that possesses antioxidant, anti‐inflammatory, and neuroprotective properties, restored these abnormalities 1 . Recently, two meta‐analyses were conducted on individuals with schizophrenia (Table S1).…”
Section: Continuous Variables K N Smd (95% Ci) P‐value I2 (%)mentioning
confidence: 99%
“…Recently, glutamate‐cysteine ligase knockout mice demonstrated that abnormal sleep–wake cycle such as sleep fragmentation and a reduction of sleep spindle in which were observed in individuals with schizophrenia 1 . Glutamate‐cysteine ligase is the key glutathione synthesis 1 .…”
Section: Continuous Variables K N Smd (95% Ci) P‐value I2 (%)mentioning
confidence: 99%
See 1 more Smart Citation